Strategy and Handling of Slum Areas in Titi Kuning Village - Arwynta Nasution; Abdiyanto; Cut Nuraini (International Journal of Society and Law, 2024)
This study aims to 1) identify the existing condition of slum areas in Titi Kuning Village, Medan Johor District with 7 aspects, namely building aspects, environmental road aspects, environmental drainage aspects, drinking water availability aspects, wastewater management aspects, waste management and fire protection aspects and 2) find out the problems of flooding/inundation and building response to flooding/inundation in slum areas in Titi Kuning Village, Medan District Johor. The population in the study is Titi Kuning Village, Medan Johor District with a sample using total sampling in order to cover the entire slum area in Titi Kuning Village. Titi Kuning Lingkungan 15 Village which was applied as a sample in this study which was referred to as data analysis techniques including: Qualitative Analysis Techniques and Qualitative Analysis Techniques. The results of the study are 1) The causes of slums in Titi Kuning Village are as follows: Settlement and Socio-Economic Conditions (Titi Kuning Village has settlements with uninhabitable houses, limited access or no access to clean water and inadequate sanitation, as well as lack of public services, settlement density is not too high, with 35% rental houses and 65% self-owned houses, The average income of the population ranges from 1 to 3 million per month, mostly native, with 97% of locals and 3% of immigrants). 2) Building Response to Residential Land and Relationship with Flooding/Inundation on Land Characteristics, namely Settlements in Titi Kuning Village are located on land with waterlogging, Building responses that are not in accordance with land conditions cause further damage when it rains. This conclusion shows that the problem of slums and inundation in Titi Kuning Village is caused by various factors including socio-economic conditions, inadequate infrastructure, and lack of good planning and coordination. Handling efforts require an integrated approach from various parties.